LINGUOPOETICS OF WORDS WITH THE MEANING OF THE LION IN "RIYOZU-D-DAVLA" BY OGAHIE (TAMADDUN NURI JURNALI, 2024)
This article provides an overview of the historical works of Ogahi, in particular the role of zoonyms in the creation of the artistic representation in “Riyozu-d-davla”, the expression and use of words with the meaning of lion in different languages in the work, and the poetic means created with the help of these words.